Citizen science identifies the effects of nitrogen dioxide and other environmental drivers on tar spot of sycamore. (July 2016) - Gosling, Laura; Ashmore, Mike; Sparks, Tim; Bell, Nigel
Abstract: Elevated sulphur dioxide (SO2 ) concentrations were the major cause of the absence of symptoms of tar spot ( Rhytisma acerinum ) of sycamore ( Acer pseudoplatanus ), in urban areas in the 1970s. The subsequent large decline in SO2 concentrations has not always been accompanied by increased tar spot symptoms, for reasons that have remained unresolved. We used a large citizen science survey, providing over 1000 records across England, to test two competing hypotheses proposed in earlier studies. We were able to demonstrate the validity of both hypotheses; tar spot symptoms were reduced where there were fewer fallen leaves as a source of inoculum, and elevated nitrogen dioxide concentrations reduced tar spot symptoms above a threshold concentration of about 20 μg m −3 . Symptom severity was also lower at sites with higher temperature and lower rainfall. Our findings demonstrate the power of citizen science to resolve competing hypotheses about the impacts of air pollution and other environmental drivers. Highlights: Citizen scientists quantified tar spot symptoms on sycamore across England. Tar spot symptom severity was lower where there were fewer fallen leaves. Tar spot symptom severity was lower at sites with NO2 concentrations above 20 μg m −3 Citizen science is a valuable tool to test hypotheses about air pollution impacts. Abstract : Citizen science resolves competing hypotheses on environmental drivers of tar spot.